2021
DOI: 10.3390/ijms22147684
|View full text |Cite
|
Sign up to set email alerts
|

Sympatholytic Mechanisms for the Beneficial Cardiovascular Effects of SGLT2 Inhibitors: A Research Hypothesis for Dapagliflozin’s Effects in the Adrenal Gland

Abstract: Heart failure (HF) remains the leading cause of morbidity and death in the western world, and new therapeutic modalities are urgently needed to improve the lifespan and quality of life of HF patients. The sodium-glucose co-transporter-2 (SGLT2) inhibitors, originally developed and mainly indicated for diabetes mellitus treatment, have been increasingly shown to ameliorate heart disease, and specifically HF, in humans, regardless of diabetes co-existence. Indeed, dapagliflozin has been reported to reduce cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 71 publications
(120 reference statements)
1
20
0
1
Order By: Relevance
“…Notably, in that same study, the ketone body β-hydroxybutyrate (or 3-hydroxybutyrate) was shown to block FFAR3 and antagonize its pro-sympathetic hyperactivity in neurons [ 21 ] ( Figure 2 ). On the other hand, sodium/glucose co-transporter (SGLT)-2 inhibitors, such as dapagliflozin and empagliflozin (anti-diabetic/diuretic drugs with a plethora of beneficial cardiovascular effects that have been coming to light at an accelerating pace), increase ketone body (including β-hydroxybutyrate) production in the heart and blood vessels [ 90 , 91 ]. Given that dapagliflozin and empagliflozin have been shown to possess sympatholytic properties that mediate, at least in part, their beneficial effects in chronic human heart failure [ 92 ], it is tempting to speculate that the sympatholytic effects of SGLT2 inhibitor drugs are mediated, at least partially, by the b-hydroxybutyrate-mediated blockade of FFAR3 signaling in sympathetic neurons, which normally raises cardiac norepinephrine levels and cardiovascular sympathetic nervous system activity [ 91 ].…”
Section: Ffar3 Signaling and Cardiovascular Functionmentioning
confidence: 99%
“…Notably, in that same study, the ketone body β-hydroxybutyrate (or 3-hydroxybutyrate) was shown to block FFAR3 and antagonize its pro-sympathetic hyperactivity in neurons [ 21 ] ( Figure 2 ). On the other hand, sodium/glucose co-transporter (SGLT)-2 inhibitors, such as dapagliflozin and empagliflozin (anti-diabetic/diuretic drugs with a plethora of beneficial cardiovascular effects that have been coming to light at an accelerating pace), increase ketone body (including β-hydroxybutyrate) production in the heart and blood vessels [ 90 , 91 ]. Given that dapagliflozin and empagliflozin have been shown to possess sympatholytic properties that mediate, at least in part, their beneficial effects in chronic human heart failure [ 92 ], it is tempting to speculate that the sympatholytic effects of SGLT2 inhibitor drugs are mediated, at least partially, by the b-hydroxybutyrate-mediated blockade of FFAR3 signaling in sympathetic neurons, which normally raises cardiac norepinephrine levels and cardiovascular sympathetic nervous system activity [ 91 ].…”
Section: Ffar3 Signaling and Cardiovascular Functionmentioning
confidence: 99%
“…The fact that SGLT2 inhibitors lower blood pressure without raising heart rate implies that they may be linked to a reduction in sympathetic overactivity. Both animal models of diabetes and obesity [ 28 , 29 ] appear to have these sympathoinhibitory effects with SGLT2 inhibitors (without diabetes). When the kidneys are harmed, the brain senses this via the afferent renal nerve, increasing sympathetic outflow from the central nervous system.…”
Section: Reviewmentioning
confidence: 99%
“…A raised sympathetic tone for a long duration of time may cause advanced atherosclerosis and reduced blood flow to the kidneys, resulting in a decrease in renal function. Heart failure is also exacerbated [ 29 ]. In heart failure, overactivity of the sympathetic nervous system is linked to increased hospitalization and death.…”
Section: Reviewmentioning
confidence: 99%
“…FFAR3 is expressed in various tissues including in the heart [ 1 , 2 , 3 ] and is known to promote tissue inflammation and, as mentioned above, sympathetic nervous system (SNS) activity, neuronal firing, and NE release [ 1 , 2 , 3 ]. The latter is cardiotoxic, especially for the failing heart, as it increases myocardial oxygen/metabolic demand [ 24 , 25 ]. However, very little (virtually nothing) is currently known regarding cardiac FFAR3 signaling, per se.…”
Section: Introductionmentioning
confidence: 99%